Zi Shen Huo Luo Formula Enhances the Therapeutic Effects of Angiotensin-Converting Enzyme Inhibitors on Hypertensive Left Ventricular Hypertrophy by Interfering With Aldosterone Breakthrough and Affecting Caveolin-1/Mineralocorticoid Receptor Colocalization and Downstream Extracellular Signal-Regulated Kinase Signaling - Song, Xiaotong; Zhao, Yue; Wang, Shijun; Wang, Yuan; Chen, Qian; Zhao, Haijun; Wang, Hua; Tian, Sheng; Yu, Huayun; Wu, Zhichun (Frontiers in Pharmacology, 2020)
Left ventricular hypertrophy (LVH) is an important characteristic of hypertensive heart disease. Renin-angiotensin system (RAS) blockers have been shown to be effective drugs for the reversal of LVH. Clinical and experimental studies have shown that Zi Shen Huo Luo Formula (ZSHLF) can improve the efficacy of perindopril in the treatment of hypertensive LVH, but its mechanism is unclear . This study aimed to investigate the possible mechanism to improve the efficacy of perindopril. First, we identified 23 compounds in ZSHLF by UPLC-MS/MS analysis, among which ferulic acid, caffeic acid, vanillic acid, berberine, rutin, quercetin, kaempferol, stachydrine and tiliroside have been reported to reduce blood pressure and exhibit cardioprotective effects. Second, we treated spontaneously hypertensive rats (SHRs) with perindopril and ZSHLF for 12 continuous weeks and found that chronic use of perindopril could increase the aldosterone (ALD) levels and cause aldosterone breakthrough (ABT). ZSHLF combined with perindopril reduced the ALD levels, interfered with ABT, decreased blood pressure, improved left ventricular diastolic dysfunction, and decreased the collagen volume fraction; these effects were superior to those of perindopril alone. In vitro experiments, ALD-induced cardiomyocytes (H9c2 cells) and cardiac fibroblasts were treated with ZSHLF-containing serum, which suppressed ALD-induced cardiomyocyte hypertrophy and cardiac fibroblast proliferation, increased mineralocorticoid receptor (MR) and Cav-1 colocalization and decreased phosphorylated epidermal growth factor receptor (pEGFR) and phosphorylated extracellular signal-regulated kinase (pERK) protein expression the cells. In conclusion, ZSHLF can interfere with ABT and affect the pathological role of ALD by affecting MR and Cav-1 interactions and EGFR/ERK signaling pathway. These effects represent a possible mechanism by which ZSHLF improves the efficacy of angiotensin-converting enzyme inhibitors (ACEIs) in hypertensive LVH treatment. However, the major bioactive components or metabolites responsible for the effects and the implications of these findings in patients need further verification.